Pengaruh Desentralisasi Fiskal dan Tingkat Kemiskinan terhadap Pertumbuhan Ekonomipada Provinsi Sumaterautara - Novita Sari; Isnaini Harahap; Khairina Tambunan (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This study aims to find out the effect of fiscal decentralization and poverty levels on economic growth in North Sumatra province. This research uses quantitative methods, secondary data collection techniques with documentation using data from the Central Bureau of Statistics for each district/city in North Sumatra. . This study uses the SPSS statistical tool. Data were analyzed using multiple linear regression analysis method. The results of this study indicate that fiscal decentralization has a negative and significant effect on economic growth. This is evidenced by the fact that the tcount for the Fiscal Decentralization variable (-2.831) is smaller than the ttable (1.984) and the sig value is 0.006 <0.05. Poverty levels have a negative and significant effect on economic growth. This is evidenced by because the tcount for the Poverty Level variable (-2.664) is smaller than ttable (1.984) and the sig value is 0.009 <0.05, the decision is Ha2 rejected and Ho2 accepted. Meanwhile, the F test of Fiscal Decentralization and Poverty Level has a simultaneous and significant positive effect on Economic Growth. This is evidenced by the fact that Fcount is (11.334) greater than Ftable (3.94) and has a sig value of 0.000 <0.05. Meanwhile, in testing the coefficient of determination, the R Square value is 0.602. This shows that the independent variables, namely Fiscal Decentralization and Poverty Level, are able to explain the dependent variable, namely Economic Growth of 19.1% while the remaining 80.9% is explained by other variables outside the regression model. Keywords: Fiscal Decentralization, Poverty Level, Economic Growth